(untitled) (Indonesian Court and Justice Review, 2025)
Judicial independence is a foundational principle of democratic governance, yet it faces increasing threats in many parts of the world—including Indonesia—amid the resurgence of political populism. This study examines how the rise of populist narratives and post-pandemic political consolidation affect the independence of the judiciary in Indonesia. By analyzing political discourse, court decisions in politically sensitive cases, and institutional developments since the COVID-19 pandemic, the research identifies trends of politicization, erosion of checks and balances, and public distrust toward judicial institutions. The findings reveal a growing pattern where populist actors frame the judiciary as an elite obstacle to the "will of the people," thereby undermining its legitimacy. Moreover, executive influence over judicial appointments and budgetary controls further weakens institutional autonomy. The pandemic has exacerbated these dynamics, with emergency legislation and fast-tracked policies often bypassing judicial scrutiny. The novelty of this research lies in its intersectional analysis of judicial independence, populism, and pandemic-era governance. It contributes to both the Indonesian and global discourse on democratic backsliding by highlighting how structural and discursive tactics can be used to constrain judicial authority. The study calls for renewed safeguards—legal, institutional, and cultural—to protect judicial independence in the face of shifting political climates.